The Potential Application of Clitoria ternatea for Cancer Treatment - Purnamayanti, Anita; Budipramana, Krisyanti; Gondokesumo, Marisca Evalina (Pharmaceutical Sciences and Research, 2022)
The Clitoria ternatea flower, known as bunga telang in Indonesia, is commonly mixed with food and beverages to provide a natural blue colour. Aside from its popular culinary use, it is a traditional medicine in Indonesia for diseases in the eyes, urinary tract and skin, as well as functioning as an anti-toxin. Furthermore, recent advances in science and technology have revealed that the C. ternatea flower contains a high level of polyphenol compounds that possess anticancer activity, including saponins, tannins, steroids, triterpenoids, kaempferol, and quercetin. This review aims to identify and analyse recent articles regarding the phytochemical activities of C. ternatea flower extract as an anticancer agent. The literature on main databases from 2011 to 2021 was searched systematically using the keywords “Anticancer activity of Clitorea ternatea” and “Phytochemical activities of Clitorea ternatea flower extract against cancer cells”. The various extracts of C. ternatea flower display a moderate cytotoxic, IC50 = 21 µg/mL - 200 µg/mL, for many cancer cell lines, such as MCF-7, MDA-MB-231, CaoV-3, HEp-G2 in aquadest extract and the DLA cell line in petroleum ether extract. The bioactive compounds responsible for the anticancer effect include ternatins, delphinidin, kaempferol, quercetin, sitosterol, and tocopherols. In addition, there have been no reports of any toxic effect on normal cells (Hs27) and oral consumption in mice. According to many studies, the extract is active on multi-molecular targets, with the most conclusive effect on polymerase enzymes, whose inhibition can be an important therapeutic strategy to treat hyperproliferation in cell cancer. Therefore, the findings suggest a potential application of C. ternatea for cancer treatment.